Upaya Pengelolaan Ekosistem Mangrove Berkelanjutan di Teluk Kendari Provinsi Sulawesi Tenggara (BioWallacea : Jurnal Penelitian Biologi (Journal of Biological Research), 2023)
One of the threats posed by community and local government in the coastal area of Kendari Bay was the management of mangrove ecosystems that is not friendly, which was ignores applicable environmental laws and regulations. Aims of this research was to analyze the composition and diversity of mangrove species, the level of mangrove deforestation and degradation, and to formulate strategies for sustainable mangrove ecosystem management efforts in Kendari Bay, Southeast Sulawesi. Some of the analyzes in this research was: remote sensing system with guided classification method, vegetation analysis using line transect and plot method, description and SWOT analysis. The results showed that changes in the area of mangrove forests that occurred in 2014 to 2017 decreased by 2 ha, while from 2017 to 2020 there was an increase of 26 ha. Mangrove degradation level of Kendari Bay in 2014 to 2020 anlyzed by standard criteria for mangrove degradation of Ministry of Environment and Forestry Decree No. 201 of 2004 is categorized as damaged with tree density / ha very rare. The results of the vegetation analysis showed that were 11 mangrove species in the 5 observation stations of Kendari Bay. Rhizophora mucronata is the dominant species in the Kendari Bay mangrove community from 5 observation stations. Mngrove degradation caused by factors of economic, low of education and skills, and lack of control from the authorities. Based on the SWOT diagram and matrix, the position of the mangrove management strategy at the research location is in the third quadrant (Turn Around strategy).Key words: Upaya pengelolaan; tingkat kerusakan; mangrove.